Introducing ‘MOODLE’ as a Formative Assessment Tool: Perception of Medical Students (Medical Forum Monthly, 2023)
Objective: The purpose of this study is to determine the perception of medical students regarding the use of MOODLE as formative assessment tool.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Fazaia Ruth Pfau Medical College, Karachi from January 2023 to April 2023.Methods: A paid version of Moodle was used in this study. To be able to access Moodle, all students were provided username and password to be registered by teacher. The formative assessment was in the form of multiple-choice questions prepared by subject experts. The questions were subsequently posted on Moodle to gauge how well the fourth-year MBBS students understood the ENT material that was covered in block 1. After the formative quiz, a questionnaire was emailed to all the students to carry out the survey. The questionnaire was developed with the help of literature.Results: The findings revealed that students concluded that formative evaluation is an essential component of learning in the classroom. (Mean=3.94, SD=0.92), in recognizing challenging ideas that students are having a hard time grasping (Mean=3.99, SD= 0.95), in facilitating teachers to recognize skills that students are struggling to adapt (Mean=3.92, SD=0.96).Conclusion: Numerous pieces of literature have emphasized the value of assessments taken as formative to collect information regarding students’ progress. By conducting assessments with the help of MOODLE platform, it is easy to provide feedback to students regarding their performance. The simplicity of use and interactive features aid in raising student involvement at the same time. The students appreciated the incorporation of formative assessments and use of MOODLE.